Fibre laser soldering operation and its effect onto intermetallic compound at the solder joint: short review - Nabila, Tamar Jaya; Siti Rabiatull Aisha, Idris (Universiti Malaysia Pahang, 2019)
Nowadays the application of laser technology in microelectronic packaging has been widely implemented in many developed countries. Its flexibility on setting the parameters by following individual’s requirement, localized heating, non-contact heating, fast heating and cooling rate makes it one of the best choice for creating a joint between solder alloy and printed circuit board in microelectronic devices. Laser soldering method ease the automation process and its ability of directing the energy beam onto desired target area is seen as an advantage compared to other conventional soldering methods such as reflow soldering (infra-red and hot air), vapour phase or hot-belt soldering whereas the entire assembly is passed through an oven to form solder joint with metallurgical bonding. Meanwhile, as in conjunction to support the banned usage of lead (Pb) in electronics, the lead-free solder alloy has been proposed as the best alternative solder to replace SnPb solders. Many researchers have also studied that Sn-Ag-Cu solder alloy group have a better melting temperature that is in between 216-227 in degrees Celsius compared to Sn-Pb melting temperature (183ºC). This paper will focus on fibre laser operation with regards to soldering process and also its effect towards intermetallic compound formation at the solder joint.